The role of the Russian Orthodox Church in development of national education system of small indigenous peoples of the Yenisei province (1860–1917) - O. A. Gunter (Омский научный вестник: Серия "Общество. История. Современность")
The article is a survey research that examines the experience of the formation and development of the national education system for small indigenous peoples of the Yenisei province in the pre-revolutionary period and analyzes the role of the Russian Orthodox Church in this process. The study provides a characteristic of the regulatory and methodological framework, describes the structure of church institutions involved in the education of foreigners, and also analyzes the activities of educational institutions for the foreign population. A complex of research methods is used for the study: comparative historical, structural-functional, problemchronological, anthropological, statistical. The author comes to the conclusion that the Russian Orthodox Church played a fundamental role in the genesis of the system of national education for the indigenous small peoples of the Yenisei province in the second half of the 19th – 20th centuries.